2015
DOI: 10.1371/journal.pone.0118211
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid Stress System Drives Chemical Transfer of Fear from Sender to Receiver

Abstract: Humans can register another person’s fear not only with their eyes and ears, but also with their nose. Previous research has demonstrated that exposure to body odors from fearful individuals elicited implicit fear in others. The odor of fearful individuals appears to have a distinctive signature that can be produced relatively rapidly, driven by a physiological mechanism that has remained unexplored in earlier research. The apocrine sweat glands in the armpit that are responsible for chemosignal production con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 85 publications
(149 reference statements)
5
43
0
Order By: Relevance
“…Emotion experiences elicited in the lab are not influenced by pre-existing affective states [45]. In previous experiments (e.g., [54]), we found that when participants enter the lab for the first time their salivary cortisol levels (indicator of psychological stress) were high (e.g., de Groot et al [54], Figure 3C). As it can take more than 20-30 min for this level to decline to a "relaxed" state, being stressed on the first visit might confound the induction of happiness or neutral/calm emotional states, while at the same time, the fear induction would benefit from it.…”
Section: Emotion Induction and Sweat Collection From Donorsmentioning
confidence: 54%
See 1 more Smart Citation
“…Emotion experiences elicited in the lab are not influenced by pre-existing affective states [45]. In previous experiments (e.g., [54]), we found that when participants enter the lab for the first time their salivary cortisol levels (indicator of psychological stress) were high (e.g., de Groot et al [54], Figure 3C). As it can take more than 20-30 min for this level to decline to a "relaxed" state, being stressed on the first visit might confound the induction of happiness or neutral/calm emotional states, while at the same time, the fear induction would benefit from it.…”
Section: Emotion Induction and Sweat Collection From Donorsmentioning
confidence: 54%
“…These reasons have been explained in the Methods section and are related to the inherent difficulty of inducing emotions in a laboratory setting knowing they are also influenced by pre-existing affective states [45]. Consequently, inducing fear during the first visit when cortisol levels are known to be high [54], served to maximize the chances of success at inducing fear. The self-reported levels of emotion from the donors in our study corroborated effective induction of fear, happiness, and a calm "pleasant neutral" state by following this fixed order.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is perhaps worth considering how sexual arousal chemosignals interact with individual factors we did not specifically examine, such as testosterone levels (Gangestad, Thornhill, & Garver-Apgar, 2010;Thornhill & Gangestad, 1999), or individual differences in disgust sensitivity (Haidt, McCauley, & Rozin, 1994;Stevenson, Case, & Oaten, 2011). Finally, future work could include a wider range of measures to monitor the emotions of the scent donors and the scent recipients during the experiment (de Groot et al, 2015b;Mitchell, DiBartolo, Brown, & Barlow, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…After arriving at the laboratory and receiving a brief introduction to the study, participants were asked by a female experimenter to clean their underarms using fragrance-free wipes (e.g., de Groot, Smeets, & Semin, 2015b;Elliot, Muir, & de Catanzaro, 2017). Large cotton pads were then affixed to their underarms using surgical tape, and they were given a new white T-shirt to wear for the experiment.…”
Section: Female Scent Sample Collectionmentioning
confidence: 99%
“…Various gases are released from human bodies, including metabolic gases, while sweat VOCs and VOCs are produced by floral bacteria [51]. On the other hand, there is a lack of research on VOCs relating to human emotions, even though several studies have tested the role of sweat in human emotional interactions, such as fear sweat [52] and anger aggression [5]. These studies present the olfactory roles in emotional interactions, while the roles of chemical contents of emotional sweat had not been the focus of prior studies.…”
Section: Volatile Organic Components (Vocs)mentioning
confidence: 99%